Going to the ground (or AstroTurf): a grassroots view of regime resilience. Issue 2 (23rd February 2017) - Weiss, Meredith L.
ABSTRACT: While disproportional resources and curbs on civil and political rights clearly matter to electoral authoritarian persistence, long-term acculturation to political norms and modes of governance on the ground in such regimes – of which Singapore and Malaysia are the most durable examples – complicate transformation. A combination of what amounts to classic machine politics with the structural "assist" of sub-par elections renders electoral authoritarianism extraordinarily increasingly resilient over time, not just because it is hard or unlikely for voters to vote in new leaders, but also because the aspiring or elected opposition may end up reproducing rather than subverting key attributes of that regime. Clientelist political praxis may be highly responsive, offer direct accountability, and align with voters' rational self-interest, at least in the short term. However, its persistence impedes pursuit of new ideological or programmatic objectives, perpetuates piecemeal and inefficient allocation of resources, assumes that most voters should expect little from state policies, and discourages attention to proactive legislation, in favour of a more localized, reactive politics. A machine-oriented political regime, then, is not only exceptionally hard to shake, but suboptimal in the long term.